Not all moderate disease is the same - Identification of disability trajectories among patients with rheumatoid arthritis and moderate disease activity. - Yi Pan; Sam Norton; James M Gwinnutt; Lianne Kearsley-Fleet; Deborah P M Symmons; Mark Lunt; Adam Young; BSRBR-RA Control Centre Consortium; Kimme L Hyrich; Suzanne M M Verstappen (PLoS ONE, 2019)
Background United Kingdom guidelines for the use of biologic disease modifying anti-rheumatic drugs (bDMARDS) for rheumatoid arthritis (RA) require patients to have active disease (Disease Activity Score [DAS28] >5.1) and have failed ≥2 previous conventional synthetic DMARDs (csDMARD). Patients with moderate disease activity (MDA) do not meet these criteria, yet often have poor outcomes. This study aimed to identify trajectory groups of disability scores over three years in RA patients with MDA. Methods The study included biologic-naïve patients receiving csDMARDs only with MDA (3.2 <DAS28≤ 5.1) when recruited to the control cohort of the British Society for Rheumatology Biologics Register-RA (BSRBR-RA). Disability scores, measured using the Health Assessment Questionnaire (HAQ), were recorded every six months for three years. Trajectories of HAQ scores over follow-up were assessed using latent class growth models (LCGMs). Baseline age, gender, DAS28, symptom duration, rheumatoid factor status, number of prior csDMARDs and co-morbidities were assessed as potential predictors of group membership. Results In total, 1274 patients were included (mean age: 61 years (standard deviation: 12), 71.4% women). The best fitting model included seven HAQ trajectories. These trajectories were horizontal over follow-up and were related to baseline HAQ: very-low (6.8%, baseline (BL) HAQ: 0.22), low (11.5%, BL HAQ: 0.41), low-moderate (17.0%, BL HAQ: 0.93), moderate (13.4%, BL HAQ: 1.09), high-moderate (19.5%, BL HAQ: 1.61), severe (23.2%, BL HAQ: 1.98) and very-severe (8.6%, BL HAQ: 2.54). Higher DAS28, older age, female gender, longer disease duration and more co-morbidities were independently associated with higher HAQ trajectory group. Conclusion There is substantial heterogeneity in baseline HAQ scores in this population, and the trajectories of HAQ scores after baseline are, on average, relatively flat. As bDMARD therapy has been shown to improve HAQ scores, patients with MDA but high HAQ scores may benefit from a more aggressive approach to therapy.